Effect of Nutritional Support Containing Arginine, Glutamine and β-hydroxy-β-methylbutyrate on the Protein Balance in Patients with Major Burns - Erdem, Deniz (Turk J Anaesthesiol Reanim, 2019)
OBJECTIVE: To evaluate the effect of a supplementary nutritional product containing arginine, glutamine and β-hydroxy-β-methylbutyrate (HMB) on the nutritional parameters of patients with major burns. METHODS: In a total of 40 patients with major burns treated in the Burns Unit, standard nutritional support was administered to 20 patients, and the study product was added to the standard nutritional support of the remaining 20 patients. The biochemical laboratory test results and burn severity were recorded on the first day of treatment and on Days 14 and 28. The 40 patients were divided as the study and the control group, and their results were compared. RESULTS: An increase in the albumin, prealbumin and total protein values in the group administered with the study product was found to be statistically significant compared to the control group (p=0.021, p=0.02, p<0.001, respectively). The decreases in haemoglobin and C-reactive protein (CRP) were at the levels expected in burn trauma. CONCLUSION: The results obtained in this study demonstrated that the addition of arginine, glutamine and HMB to the nutrition of patients with burns had a positive effect on the protein balance.